Obraz przeszłości w percepcji magiczno-mitycznej, czyli pamięć w działaniu (Politeja, 2015)
The Image of the Past in Magical-Mythical Perception, or the Memory in ActionThe aim of the paper is to identify a specific type of cognitive conduct, which can be called magical-mythical perception and thinking. It is based on a relevant habitus and its principle is indistinctness (blending, blurring), where differences between diverse phenomena, memory images and notions disappear in perception and imagination, as well as between denotation and connotation. Such an indistinctness can have considerable impact on social memories. The author identifies in such a cognitive conduct the possible key to the following questions: How is it possible that we can perfectly adopt different representations of the past and internalize them as our past? How can we reconcile different representations of the past and how is it possible that diverse representations of the past merge in one social memory? Such amalgamations of various forms of representations and diverse scales of objectification can be clarified by means of the theory of magic and by means of Roland Barthes´ theory of myth. The main proposition of the paper is to identify, for the first, the unconscious structure (a habitus formed in the historical process), which defines a manner of experiencing the world, speaking about the world and making choices in that world. For the second, the criteria a person uses to select and evaluate narratives about the past.